The Internalization of Entrepreneurial Characters in Pondok Pesantren Anwarus Sholihin Purwokerto - Munjin, Munjin (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
This research is on etrepreneurhsip education in pesantren, Islamic boarding schools. It tries to answer two main questions: what attitudes to be cultivated and how to instil them into students of pesantren. So far pesantren have been generally assumed to be institutions which contribute to the increasing unemployment rate in social life. Their graduates are indeed highly competent in socio-religious affairs, in which they are even considered to be prominent figures. However, they are poor in creative economy and the utilization of natural resources. In this case, Pesantren Anwarus Sholihin, Purwokerto, tries to bridge the competence gap. The research found that pesantren Anwarus Sholihin, Purwokerto, has instilled entrepreneurial spirit into its students through providing students with learning activities and training, generating great motivation for entrepreneurship, administering internship programs, and involving students in manufacturing and marketing products, which are food products produced from their fruit and vegetable harvests. Through those activities, students are actually trained to have geneorus characters like honesty ad self-motivation and entrepreneurial skills like good teamwork, courage to take a risk, and creative and innovative thinking. Entrepreneurship education-based pesantren have proved to make a huge contribution materially and morally. Besides their being economically independent in meeting their daily economic needs, they can also create generations of student entrepreneurs who are proud to be graduates of pesantren and not easily discouraged from making efforts.